2016
DOI: 10.1186/s40064-016-1929-7
|View full text |Cite
|
Sign up to set email alerts
|

What differs between happy and unhappy people?

Abstract: This study explores the determinants (demographic, personal, behavioural, and social) by which happy and unhappy people differ. The primary sample from which the participants were chosen was a representative sample of Croatian citizens (N = 4000). On the basis of the distribution of overall happiness the sample of the highest (the happy group) and the lowest 10 % of participants (the unhappy group) were selected. The happy group (N = 400) represented the upper end of the happiness distribution, while the unhap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
3
9
0
1
Order By: Relevance
“…In that regard, authors Matz et al [ 31 ] have observed individuals’ spending capacity to positively correlate with higher levels of life satisfaction. This corroborates that prevalence of unhappy status was higher for elderly [ 32 ] or low income elderly [ 33 ], although as Ye et al [ 34 ] suggested that the traditional economic factors and demographics have low explanatory power over the cross-country differences in subjective well-being. The results further suggest that policies and programs aiming at improving financial conditions of households may end up improving overall health and wellbeing.…”
Section: Discussionsupporting
confidence: 82%
“…In that regard, authors Matz et al [ 31 ] have observed individuals’ spending capacity to positively correlate with higher levels of life satisfaction. This corroborates that prevalence of unhappy status was higher for elderly [ 32 ] or low income elderly [ 33 ], although as Ye et al [ 34 ] suggested that the traditional economic factors and demographics have low explanatory power over the cross-country differences in subjective well-being. The results further suggest that policies and programs aiming at improving financial conditions of households may end up improving overall health and wellbeing.…”
Section: Discussionsupporting
confidence: 82%
“…13,15,20 People who were healthy or had no co morbidities were found to be happier than the people with co morbidities in the study, which paralleled with studies done within India and outside. 16,17,[19][20][21][22][23]25 Individuals who met their friends and relatives regularly or were a part of a social group were found to be happier than the lonelier ones and this result was statistically significant. This finding was well supported by reported literature as well.…”
Section: Resultsmentioning
confidence: 96%
“…17,18 In the present study no differences were noted due to literacy and occupation parameters but these were contrary to studies from other countries. 13,17,19 The probable explanation would be that, less educated people had more leisure time to engage themselves in other activities which could be the source of happiness. Education may also lead to higher expectations from life which sometimes becomes more difficult to attain and hence leads to dissatisfaction in life.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those IWI indices were then continuously used to monitor the wellbeing of Croatia's citizens in the years 2005, 2007, and 2008(Kaliterna Lipovcan and Prizmic Larsen 2006aKaliterna Lipovcan et al 2011). Recently only PWI was used for monitoring the well-being of Croatia's citizens in the years , 2015, and 2016, 2017Kaliterna Lipovcan 2018).…”
mentioning
confidence: 99%